(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
This article examines the phenomenon of persistent demand for cash in the context of digitalization of the payment system. Based on data from the Bank of Russia and international studies, the factors responsible for maintaining cash in circulation are analyzed, including technological failures, the psychological need for security, financial inclusion, and the shadow economy. The aim of the study is to identify and systematize the causes of this phenomenon. The practical significance of this study lies in its substantiation of the need to preserve the cash payment infrastructure to maintain financial stability and ensure the availability of payment services for socially vulnerable groups.